2019
DOI: 10.1016/j.psyneuen.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk for circulating reproductive hormone levels and their influence on hippocampal volume and depression susceptibility

Abstract: Highlights Hippocampal volume and depression risk have been linked to reproductive hormones. We generated polygenic risk scores (PRS) for four reproductive hormones. PRS for higher estradiol predicted smaller hippocampal subfield volumes. None of the PRSs predicted postpartum or major depression risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 85 publications
1
10
0
Order By: Relevance
“…45 Another study explored the association between PRS for 4 reproductive hormones (estradiol, progesterone, prolactin, and testosterone) and subfield volumetry in a sample of MDD with an average age of 50 ± 8.1. 46 The study reported that PRS for estradiol predicted reduced volumes of the right and left subiculum (right: Although GRS-AD correlated strongly with the percentage change in thickness across the whole hippocampal complex (β = −0.25, p = 0.048) and ERC (β = −0.35, p = 0.009), no significant results were found between the risk scores and thickness in any specific hippocampal subfield.…”
Section: Polygenic Risk Scoresmentioning
confidence: 93%
“…45 Another study explored the association between PRS for 4 reproductive hormones (estradiol, progesterone, prolactin, and testosterone) and subfield volumetry in a sample of MDD with an average age of 50 ± 8.1. 46 The study reported that PRS for estradiol predicted reduced volumes of the right and left subiculum (right: Although GRS-AD correlated strongly with the percentage change in thickness across the whole hippocampal complex (β = −0.25, p = 0.048) and ERC (β = −0.35, p = 0.009), no significant results were found between the risk scores and thickness in any specific hippocampal subfield.…”
Section: Polygenic Risk Scoresmentioning
confidence: 93%
“…Considering the limited evidence for the role of these metabolites in the mechanism underpinning the antiinflammatory and neurogenic activities of ω-3 PUFAs in the context of depression, we used our aforementioned, validated in vitro model of 'depression in a dish' [13,20,21,[29][30][31][32][33] exposing immortalised human hippocampal progenitor cell line HPC0A07/03C to candidate 'depressogenic' cytokines, IL1β, IL6 and IFN-α, resulting in a reduction in neurogenesis and an increase in neuronal apoptosis [13,20,21]. In order to identify the lipid species or families of COX-, LOX-or CYP450-derived mediators putatively involved in the anti-inflammatory and neuroprotective effects exerted by ω-3 PUFAs, we pre-treated cells with EPA/DHA with or without a selective inhibitor of COX-, LOX-or CYP450 enzymes, and then directly exposed cells to candidate metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…GWASs from European descents [74] and from the Korean population [47] have identified associations of SNPs related to E2 biosynthesis and ERs with SCZ. More recent GWASs have identified that a genetic risk (E2 polygenic risk score) for higher plasma E2 is negatively associated with hippocampal volume, but not with an increased risk of major depressive disorder or postpartum depression [75]. However, the largest GWAS of anxiety traits to date was able to identify genome-wide significant associations near genes involved with the ERα (ESR1) [76].…”
Section: Genetics Of Schizophrenia and Bipolar Disordermentioning
confidence: 99%